"Behind the Words": Negotiating Literal/Figurative Sense When Translating the Lyrics to a Children's Song in Bilingual Preschool. Issue 2 (4th March 2018) - Kultti, Anne; Pramling, Niklas
ABSTRACT: This study investigates how 6- to 7-year-old children in a bilingual preschool together with their teachers take on the challenge of translating the lyrics to a children's song from Finnish to English. With an interest in how translation activities can engage children in communication and metacommunication, and facilitate the development of linguistic and metalinguistic awareness, how a decisive matter of translation – that of taking an utterance literally and/or metaphorically – is negotiated among participants is more specifically scrutinized. The study takes a sociocultural theoretical perspective on learning and communication. The study shows how this kind of activity allows teachers to scaffold children engaging in talk about linguistic and metalinguistic matters, pivotal to their language development and comprehension of this kind of text.